Association of plasma levels of lipid and polychlorinated biphenyls in Iranian adult - Aminian, Omid; Moinfar, Zeinab; Eftekhari, Sahar; Esser, André; Schettgen, Thomas; Felten, Michael; Kaifie, Andrea; Kraus, Thomas (Heliyon, 2020)
Background: Exposure to Polychlorinated biphenyls (PCBs) continues over the world through seafood consumption and indoor exposure to building materials containing PCB. This study aimed to assess the relationship between plasma level of PCB congeners and lipid profile and Body Mass Index (BMI) as well. Methods: The study population consisted of 181 Iranian adults. Data on BMI, plasma concentration of PCB congeners and serum level of lipid profile including Triglyceride, low-density lipoproteins and high-density lipoproteins, recruited from database of a project entitled “Occupational and environmental exposure to PCBs in Iran”. Multiple linear regression analysis of associations between different quartiles of PCB congeners and various lipid fractions and BMI have been conducted. Results: A linear increase in average serum Triglyceride and low-density lipoproteins (LDL) levels of participants in first, second, third and fourth quartiles of some PCB congeners was obtained. Following adjustment for age, gender, diet and other variables, only the association between different quartiles of PCB 138, PCB 153, PCB 118 and PCB sum and TG remained statistically significant. Conclusion: The study showed a significant positive relation between plasma PCBs concentrations and serum level of TG in the study population with normal PCBs levels.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Biological sciences; Body mass index; Endocrinology; HDL; Health sciences; LDL; Polychlorinated biphenyls; Public health; Serum lipid; Triglyceride